Comunicação científica e mediação da informação em mídia social: relato de experiência dos eventos organizados pela Comissão Diálogos de Pesquisa do PPGCI/UFF - de Almeida, Camilla Castro; Mendes, Juliana Maia; dos Santos, Vinicius Ribeiro Soares; de Souza, Elizabete Gonçalves; de Oliveira, Lucia Maria Velloso (Information Research an international electronic journal, 2025)
Introduction. ‘Research dialogues’ is a scientific dissemination event developed by a committee associated with the Information Science Postgraduate Program of the Universidade Federal Fluminense (Rio de Janeiro, Brazil). As a lecture series, it allows the exchange of knowledge among a specialized community, through the presentation of doctoral and post-doctoral reports, however, it is not restricted to this, seeking to get closer to undergraduate students. This study aims to outline the activities carried out by the committee between 2020 and 2024, covering 20 editions of the event. Method. It uses the theoretical framework of mediation to analyze and interpret the results regarding the audience profile and the evaluation of these editions. The methodology adopts a descriptive, qualitative-quantitative approach typical of an experience report. Results. The results indicate that the Committee organizes events that focus on two main categories: 1) post-doctoral internship closing seminars and 2) doctoral research meetings. These events effectively disseminate scientific knowledge and foster closer ties between postgraduate and undergraduate studies. Conclusion. They contribute significantly to scientific literacy by facilitating direct mediation through dialogue, questioning, and reflection among presenters, facilitators, and audiences.